Brief behavioral activation program for students with depressive symptoms (Journal on studies and research of academic knowledge, 2022)
The objective of the present investigation was to examine the efficacy of a BATD program in a group of university students with depressive symptoms. The sample consisted of 6 university students with mild to severe levels of depression who participated in BATD sessions and a control group made up of 6 university students with similar levels of depression who did not receive any intervention. Decreased levels of depression were recorded in the study group compared to the control group. The clinical implications of the results and their limitations are discussed.
Keywords: Behavioral Activation; BATD; Depression; University Students